Pleiotropic effects of extended blockade of CSF1R signaling in adult mice. Issue 2 (20th March 2014) - Sauter, Kristin A.; Pridans, Clare; Sehgal, Anuj; Tsai, Yi Ting; Bradford, Barry M.; Raza, Sobia; Moffat, Lindsey; Gow, Deborah J.; Beard, Philippa M.; Mabbott, Neil A.; Smith, Lee B.; Hume, David A.
Abstract : Prolonged anti‐CSF1R prevents age‐dependent bone loss in female mice, without the phenotypic consequences of the CSF1R and CSF1 null mutations. Abstract : We investigated the role of CSF1R signaling in adult mice using prolonged treatment with anti‐CSF1R antibody. Mutation of the CSF1 gene in the op/op mouse produces numerous developmental abnormalities. Mutation of the CSF1R has an even more penetrant phenotype, including perinatal lethality, because of the existence of a second ligand, IL‐34. These effects on development provide limited insight into functions of CSF1R signaling in adult homeostasis. The carcass weight and weight of several organs (spleen, kidney, and liver) were reduced in the treated mice, but overall body weight gain was increased. Despite the complete loss of Kupffer cells, there was no effect on liver gene expression. The treatment ablated OCL, increased bone density and trabecular volume, and prevented the decline in bone mass seen in female mice with age. The op/op mouse has a deficiency in pancreatic β cells and in Paneth cells in the gut wall. Only the latter was reproduced by the antibody treatment and was associated with increased goblet cell number but no change in villus architecture. Male op/op mice are infertile as a result of testosterone insufficiency. Anti‐CSF1R treatment ablated interstitial macrophages in the testis, but there was no sustained effect on testosterone or LH. The results indicate an ongoing requirement for CSF1R signaling in macrophage and OCL homeostasis but indicate that most effects of CSF1 and CSF1R mutations are due to effects on development.